Physiological and molecular aspects of degradation of plant polysaccharides by fungi: What have we learned from Aspergillus?. Issue 8 (15th May 2013) - Culleton, Helena; McKie, Vincent; de Vries, Ronald P.
Abstract Plant biomass is the most abundant and usable carbon source for many fungal species. Due to its diverse and complex structure, fungi need to produce a large range of enzymes to degrade these polysaccharides into monomeric components. The fine‐tuned production of such diverse enzyme sets requires control through a set of transcriptional regulators. Aspergillus has a strong potential for degrading biomass, thus this genus has become the most widely studied group of filamentous fungi in this area. This review examines Aspergillus as a successful degrader of plant polysaccharides, and reviews its potential in many industries such as biofuel and as a production host of homologous and heterologous proteins.